Analisis Perbedaan Peningkatan Keterampilan pada Penyuluhan Kesehatan Menggunakan Survivor dengan Non Survivor tentang SADARI pada Wanita Subur di Kota Palangka Raya - Rena Oki Alestari; Evy Kasanova; Stefanicia Stefanicia (Jurnal Surya Medika (JSM), 2022)
Background: Cancer is one of the leading causes of death worldwide. The government’s efforts in the early detection of breast cancer have not been achieved. The Purpose of the Study: To analyze the improvement difference in skills of health education by a survivor with the non-survivors of SADARI on women in their fertile period. Methods: This study used quasi-experimental research with a pretest-posttest control group design. There were 78 respondents of 20-30 years old women in their fertile period that were randomly selected in the Prenggan district. This study used the skill assessment forms of SADARI, modules, and leaflets. The data was analyzed using the Independent sample T-test. Results: There was a significant difference in skills improvement between survivor and non-survivor (activist) counseling with ρ=0,000< 0,05. Conclusions: Survivors as a resource improve skills about SADARIon women in their fertile period.